High Cure Rates With Grazoprevir-Elbasvir With or Without Ribavirin Guided by Genotypic Resistance Testing Among Human Immunodeficiency Virus/Hepatitis C Virus–coinfected Men Who Have Sex With Men. (13th August 2018) - Braun, Dominique L; Hampel, Benjamin; Kouyos, Roger; Nguyen, Huyen; Shah, Cyril; Flepp, Markus; Stöckle, Marcel; Conen, Anna; Béguelin, Charles; Künzler-Heule, Patrizia; Nicca, Dunja; Schmid, Patrick; et al.
Abstract : We treated 122 human immunodeficiency virus/hepatitis C virus-infected individuals with grazoprevir/elbasvir ± ribavirin for 12–16 weeks and achieved a sustained virological response rate of 99%. In genotype 1a infected individuals, treatment duration was guided by presence of baseline resistance-associated substitutions. Abstract: Background: This study was performed to investigate the efficacy and safety of grazoprevir-elbasvir guided by baseline resistance-associated substitutions (RASs) in the Swiss HCVree Trial. Methods: We performed hepatitis C virus (HCV) RNA screening among all men who have sex with men (MSM) enrolled in the Swiss HIV Cohort Study. Individuals with replicating HCV genotype 1 or 4 infection were eligible for grazoprevir-elbasvir treatment. Genotype 1a–infected individuals with baseline RASs and genotype 4–infected individuals with prior failure of HCV treatment received 16 weeks of grazoprevir-elbasvir combined with ribavirin. All other individuals received 12 weeks of grazoprevir-elbasvir alone. Patients reporting unprotected sex with occasional partners were offered a HCV risk reduction–oriented behavioral intervention. Results: We screened 3722 MSM and identified 177 (4.8%) with replicating infection. A total of 122 individuals (3.3%) were eligible for study treatment. Six of 76 patients infected with genotype 1a (7.3%) harbored baseline RASs. Sustained virological response after 12 weeks of follow-up was achieved in 121 patients (99%), including all with genotype 1a infection. Overall, 8 serious adverse events occurred, none of which was related to the study drug. Seventy-five percent of eligible MSM participated in the risk counseling program. Conclusions: Grazoprevir-elbasvir for 12 or 16 weeks, with or without ribavirin, achieved high cure rates and had an excellent safety profile. Unique to other studies, the treatment duration was guided by the presence of baseline RASs among genotype 1a–infected individuals, and the treatment phase was accompanied by an HCV risk reduction–oriented behavioral intervention. This successful population-wide treatment approach lays the groundwork to achieve HCV elimination in coinfected MSM. Clinical Trials Registration: NCT02785666